The Influence of South Korea Drama and Country of Origin on Brand Image and Purchase Intention of South Korea Cosmetics by Female Student in University of Mataram (Global Journal of Management and Business Research, 2020)
The objectives of this research is to analyze the influence of South Korean drama and country of origin on brand image, to analyze the influence of South Korean drama and country of origin on purchase intention, to analyze the influence of brand image on purchase intention. This research is associative explanatory research. The samples in this study is UNRAM students who know about South Korean drama and South Korean cosmetics. Data collection tools is questionnaires. The data analysis tool used is SEM (Structural Equation Modeling), which is operated with PLS. The results of this study indicate that South Korean Drama has a positive and significant effect on Brand Image, Country of origin has a positive and significant effect on Brand image, South Korean Drama has a positive and significant effect on Purchase Intention.
Keywords: south korean drama; country of origin; brand image; purchase intention